2022
DOI: 10.31729/jnma.7237
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary Syndrome of Menopause among Postmenopausal Women in a Tertiary Care Centre: A Descriptive Cross-sectional Study

Abstract: Introduction: Genitourinary syndrome of menopause incorporates vulvovaginal and lower urinary tract symptoms related to estrogen deficiency which affects more than half of postmenopausal women. This study aimed to find out the prevalence of genitourinary syndrome of menopause among postmenopausal women attending a tertiary care center. Methods: A descriptive cross-sectional study was conducted at the Department of Obstetrics and Gynaecology of tertiary care hospital from October 2019 to April 2021 after obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 18 publications
0
19
0
1
Order By: Relevance
“…A pesar de su alta prevalencia, el SGUM sigue siendo extremadamente infradiagnosticado (3,25), en parte por la resistencia que muestran las mujeres a buscar ayuda, ya sea por vergüenza o como resultado de considerarlo como una característica normal del envejecimiento natural, sin desconocer la renuencia de los profesionales de la salud a la hora de abordar estos problemas (26)(27)(28)(29). Se constituye necesario establecer programas de conciencia, acerca de la educación y la capacitación de este síndrome entre las mujeres en posmenopausia, a fin de evitar las catastróficas consecuencias en su calidad de vida.…”
Section: Discussionunclassified
“…A pesar de su alta prevalencia, el SGUM sigue siendo extremadamente infradiagnosticado (3,25), en parte por la resistencia que muestran las mujeres a buscar ayuda, ya sea por vergüenza o como resultado de considerarlo como una característica normal del envejecimiento natural, sin desconocer la renuencia de los profesionales de la salud a la hora de abordar estos problemas (26)(27)(28)(29). Se constituye necesario establecer programas de conciencia, acerca de la educación y la capacitación de este síndrome entre las mujeres en posmenopausia, a fin de evitar las catastróficas consecuencias en su calidad de vida.…”
Section: Discussionunclassified
“…Two studies were performed in a symptomatic Chinese population 15,17 and a convenience sample of Nepalese women presenting to a gynecologic clinic. 16 Inclusion criteria for some of the studies required experiencing one or more symptoms of VVA, thus making the comparison of prevalence estimates complex. Across studies, the authors noted that the most commonly self-reported symptom was vaginal dryness (ranging from 50% to 100%), and the most observed sign was decreased moisture.…”
Section: Prevalence Of Gsmmentioning
confidence: 99%
“…Conceivable are dominant subtype presentations, for example, genital symptom cluster dominance, urinary symptom cluster dominance, sexual symptom cluster dominance, or multicluster dominance. Particularly for sexually active women, there is ample evidence that genital tissue changes have a marked effect on sexual functioning, [12][13][14][15][16] most often expressed as dyspareunia with or without descriptors of tissue damage (eg, postcoital bleeding). Perhaps dyspareunia should be considered a cardinal (at least in sexually active women) or obligatory symptom, or perhaps a separate symptom within the class of sexual symptoms.…”
Section: Prevalence Of Gsmmentioning
confidence: 99%
See 2 more Smart Citations